2019
DOI: 10.5114/hpr.2019.84213
|View full text |Cite
|
Sign up to set email alerts
|

Depression and marital satisfaction: the mediating role of sexual satisfaction and perceived partner acceptance in women after mastectomy

Abstract: health psychology report • volume 7(2), 9 original article background Diagnosis and treatment of breast cancer disrupts women's functioning on both individual and dyadic levels. The main objective of the present study was to examine whether the partner's acceptance of the woman and her sexual satisfaction can play a key role in mediating the relationship between depression and marital satisfaction in women treated for breast cancer after mastectomy. participants and procedure The sample consisted of 97 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Its high level was associated with higher perceived support from the partner. This shows the importance of a satisfactory sexual life for a happy marriage [ 57 , 61 ]. Many studies have shown that sexual satisfaction effectively diversifies satisfied and dissatisfied relationships—couples with higher levels of sexual satisfaction were more content [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its high level was associated with higher perceived support from the partner. This shows the importance of a satisfactory sexual life for a happy marriage [ 57 , 61 ]. Many studies have shown that sexual satisfaction effectively diversifies satisfied and dissatisfied relationships—couples with higher levels of sexual satisfaction were more content [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study evaluating the relationship between depression and anxiety and pain catastrophising in cancer patients, it was found that the depression scores of the patients were normal but the anxiety scores were high, the depression and anxiety were related, and the pain catastrophising increased with the severity of depression and anxiety. Cancer pa- tients desire emotional support and the availability of someone with whom they can talk about their fears and concerns [17]. There are many emotional and behavioural reactions starting from the diagnosis and continuing during and after treatment in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between middle-aged women’s fertility changes and their mental health [ 10 ] shows that improving their mental health requires more accurate identification of the relationship between the factors affecting this cycle. Gender roles may influence psychological reactions related to menopause, such as depression and stress [ 11 ], and climacteric changes affecting these roles may convert menopause into a critical period.…”
Section: Introductionmentioning
confidence: 99%